Kinerja Pegawai Pada Fakultas Ilmu Pendidikan Universitas Negeri Makassar - Syamsurijal Basri; abdul saman (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This study examines the employees performance at the Faculty of Education, Makassar State University. The research method used was qualitative with an exploratory approach. The data source in this study involved seven participants. Data analysis techniques used are data reduction, data exposure and conclusion drawing or data verification. The results showed that the Performance of Employees at the Faculty of Education, Makassar State University showed that: (1) The speed of employees in completing work was optimal, employee discipline was quite high, work performed could be completed on time, providing convenience in service, in carrying out services in accordance with a work schedule that has been set. (2) The ability of employees as a whole is quite optimal, work is done manually and uses computer technology, the ability of employees to operate computers in carrying out their tasks is still lacking. (3) Employee initiatives are not optimal, Most employees work if instructed by the leadership, are less creative in carrying out work, there are some employees working time to relax, only a few employees can find their own solutions to work problems.